Command governors for constrained nonlinear systems - Angeli,D; Mosca,E (IEEE Transactions on Automatic Control, 1999)
A method is described for set-point tracking in nonlinear systems when pointwise-in-time input and/or state inequality constraints are to be enforced. It consists of adding to a primal compensated system a nonlinear device called command governor (CG) whose action is based on the current state, set-point, and prescribed constraints. The CG selects at any time the system input via a receding-horizon strategy from a virtual sequence amongst all possible command sequences by solving a constrained quadratic optimization problem. Provided that the initial state be admissible, the overall system is proved to fulfill the constraints and have desirable performance stability properties.